Gamification based assessment: A Test Anxiety Reduction through Game Elements in Quizizz Platform - Muhammad Dafit Pitoyo (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
Test anxiety always makes students afraid of doing the test because they probably think that they will fail. To overcome the problem, the teacher then used gamification based assessment. Furthermore, the study investigate the category of students test anxiety, students’ attitudes toward Quizizz and the students’ preference toward the elements of game in Quizizz. This study is case study which the data were collected by using observation, interview and questionnaires. The participants of this study were 14 students in English course in Solo. The sampling used by the researcher was purposive sampling. The results of this study showed the category of students test anxiety considered moderately high, the students’ attitude toward Quizizz in reducing test anxiety also considered high (M= 3.94) and the kinds of elements of game which students prefer most were Points (M= 4.357), Test report (M= 3.929), Leader board (M=3.714), Time restriction (M=3.357), Profile (M= 3.429) and Meme (M= 3.357). The implication of this study is Quizizz successfully reduce test anxiety because of the use of game elements in that application. Thus, it is a good option for teachers to use Quizizz on the exam.